Electrochemical oxidation of cholesterol - Morzycki, Jacek W.; Sobkowiak, Andrzej (Beilstein Journal of Organic Chemistry, 2015)
Indirect cholesterol electrochemical oxidation in the presence of various mediators leads to electrophilic addition to the double bond, oxidation at the allylic position, oxidation of the hydroxy group, or functionalization of the side chain. Recent studies have proven that direct electrochemical oxidation of cholesterol is also possible and affords different products depending on the reaction conditions.
Keywords: allylic oxidation; cholesterol; electrochemical halogenation; electrochemical oxidation

(untitled) - Morzycki, J. W. (Steroids, 2014)

Steroid Reactions: An Outline for Organic Chemists - Djerassi, C. (Holden-Day, Inc., 1963)

Organic Reactions in Steroid Chemistry - Fried, J.; Edwards, J. A. (van Nostrand Reinhold Company, 1972)

(untitled) - Schroepfer, G. J., Jr (Physiol. Rev., 2000)

(untitled) - Wentworth, P., Jr; Nieva, J.; Takeuchi, C.; Galve, R.; Wentworth, A. D.; Dilley, R. B.; DeLaria, G. A.; Saven, A.; Babior, B. M.; Janda, K. D.; Albert Eschenmoser, A.; Lerner, R. A. (Science, 2003)

(untitled) - Brinkhorst, J.; Nara, S. J.; Pratt, D. A. (J. Am. Chem. Soc., 2008)

(untitled) - Derewiaka, D.; Molińska, E. (Food Chem., 2015)

(untitled) - Umetani, M.; Ghosh, P.; Ishikawa, T.; Umetani, J.; Ahmed, M.; Mineo, C.; Shaul, P. W. (Cell Metab., 2014)

(untitled) - Lim, W. L. F.; Martins, I. J.; Martins, R. N. (J. Genet. Genomics, 2014)

(untitled) - Björkhem, I. (Biochimie, 2013)

(untitled) - Sottero, B.; Gamba, P.; Gargiulo, S.; Leonarduzzi, G.; Poli, G. (Curr. Med. Chem., 2009)

(untitled) - De Weille, J.; Fabre, C.; Bakalara, N. (Biochem. Pharmacol., 2013)

(untitled) - Miyoshi, N.; Iuliano, L.; Tomono, S.; Ohshima, H. (Biochem. Biophys. Res. Commun., 2014)

Quantitative Analysis of Steroids - Görög, S. (Elsevier Scientific Publishing Company, Inc., 1983)

(untitled) - Steckhan, E. (Angew. Chem., Int. Ed., 1986)

(untitled) - Shono, T.; Matsumura, Y.; Inoue, K. (J. Am. Chem. Soc., 1984)

Organic Electrochemistry - Simonet, J.; Pilard, J. F. (Electrogenerated reagents, 2001)

(untitled) - Barton, D. H. R.; Doller, D. (Acc. Chem. Res., 1992)

(untitled) - Bovicelli, P.; Lupattelli, P.; Mincione, E.; Prencipe, T.; Curci, R. (J. Org. Chem., 1992)

(untitled) - Sawyer, D. T.; Sobkowiak, A.; Matsushita, T. (Acc. Chem. Res., 1996)

(untitled) - Barton, D. R. H. (Tetrahedron, 1998)

(untitled) - Maki, S.; Konno, K.; Takayama, H. (Tetrahedron Lett., 1997)

(untitled) - Barton, D. H. R.; Boivin, J.; Gastiger, M.; Morzycki, J. W.; Hay-Motherwell, R. S.; Motherwell, W. B.; Ozbalik, N.; Schwartzentruber, K. M. (J. Chem. Soc., Perkin Trans. 1, 1986)

(untitled) - Balavoine, G.; Barton, D. H. R.; Boivin, J.; Gref, A.; Le Coupanec, P.; Ozbalik, N.; Pestana, J. A. X.; Rivière, H. (Tetrahedron, 1988)

(untitled) - Barton, D. H. R.; Sobkowiak, A. (New J. Chem., 1996)

(untitled) - Barton, D. H. R.; Gökturk, A. K.; Morzycki, J. W.; Motherwell, W. B. (J. Chem. Soc., Perkin Trans. 1, 1985)

(untitled) - Oloo, W. N.; Feng, Y.; Iyer, S.; Parmelee, S.; Xue, G.; Que, L. (New J. Chem., 2013)

(untitled) - Barton, D. H. R.; Hu, B.; Li, T.; MacKinnon, J. (Tetrahedron Lett., 1996)

(untitled) - Sheu, C.; Richert, S. A.; Cofre, P.; Ross, B., Jr; Sobkowiak, A.; Sawyer, D. T.; Kanofsky, J. R. (J. Am. Chem. Soc., 1990)

(untitled) - Kang, C.; Sobkowiak, A.; Sawyer, D. T. (Inorg. Chem., 1994)

(untitled) - Sheu, C.; Sobkowiak, A.; Zhang, L.; Ozbalik, N.; Barton, D. H. R.; Sawyer, D. T. (J. Am. Chem. Soc., 1989)

(untitled) - Barton, D. H. R.; Salgueiro, M. C.; MacKinnon, J. (Tetrahedron, 1997)

(untitled) - Takeya, T.; Egawa, H.; Inoue, N.; Miyamoto, A.; Chuma, T.; Kotani, E. (Chem. Pharm. Bull., 1999)

(untitled) - Okamoto, I.; Funaki, W.; Nobuchika, S.; Sawamura, M.; Kotani, E.; Takeya, T. (Chem. Pharm. Bull., 2005)

(untitled) - Okamoto, I.; Funaki, W.; Nakaya, K.; Kotani, E.; Takeya, T. (Chem. Pharm. Bull., 2004)

(untitled) - Wu, X.; Song, C.; Cheng, F.; Zhang, W. (J. Electroanal. Chem., 1992)

(untitled) - Lee, J. H.; Shoeman, D. W.; Kim, S.-S.; Csallany, A. S. (Int. J. Food Sci. Nutr., 1997)

(untitled) - Maki, S.; Konno, K.; Ohba, S.; Takayama, H. (Tetrahedron Lett., 1998)

(untitled) - Kowalski, J.; Łotowski, Z.; Morzycki, J. W.; Płoszyńska, J.; Sobkowiak, A.; Wilczewska, A. Z. (Steroids, 2008)

(untitled) - Milisavljević, S.; Vukićević, R. D. (J. Serb. Chem. Soc., 2004)

(untitled) - Milisavljević, S.; Wurst, K.; Laus, G.; Vukićević, M. D.; Vukićević, R. D. (Steroids, 2005)

(untitled) - Kowalski, J.; Płoszyńska, J.; Sobkowiak, A.; Morzycki, J. W.; Wilczewska, A. Z. (J. Electroanal. Chem., 2005)

(untitled) - Morzycki, J. W.; Łotowski, Z.; Siergiejczyk, L.; Wałejko, P.; Witkowski, S.; Kowalski, J.; Płoszyńska, J.; Sobkowiak, A. (Carbohydr. Res., 2010)

(untitled) - Tomkiel, A. M.; Brzezinski, K.; Łotowski, Z.; Siergiejczyk, L.; Wałejko, P.; Witkowski, S.; Kowalski, J.; Płoszyńska, J.; Sobkowiak, A.; Morzycki, J. W. (Tetrahedron, 2013)

(untitled) - Tomkiel, A. M.; Kowalski, J.; Płoszyńska, J.; Siergiejczyk, L.; Łotowski, Z.; Sobkowiak, A.; Morzycki, J. W. (Steroids, 2014)

(untitled) - Tomkiel, A. M.; Biedrzycki, A.; Płoszyńska, J.; Naróg, D.; Sobkowiak, A.; Morzycki, J. W. (Beilstein J. Org. Chem., 2015)

(untitled) - Hosokawa, Y.-Y.; Hakamata, H.; Murakami, T.; Aoyagi, S.; Kuroda, M.; Mimaki, Y.; Ito, A.; Morosawa, S.; Kusu, F. (Electrochim. Acta, 2009)

(untitled) - Hosokawa, Y.-Y.; Hakamata, H.; Murakami, T.; Kusu, F. (Tetrahedron Lett., 2010)

(untitled) - Hojo, K.; Hakamata, H.; Ito, A.; Kotani, A.; Furukawa, C.; Hosokawa, Y.-Y.; Kusu, F. (J. Chromatogr., A, 2007)

(untitled) - Pollegioni, L.; Piubelli, L.; Molla, G. (FEBS J., 2009)

(untitled) - Stępień, A. E.; Gonchar, M. (Acta Biochim. Pol., 2013)

(untitled) - Rahman, M. M.; Li, X.; Kim, J.; Lim, B. O.; Ahammad, A. J. S.; Lee, J.-J. (Sens. Actuators, B, 2014)

(untitled) - Fang, K.-C.; Chu, C.-H.; Hsu, C.-P.; Kang, Y.-W.; Fang, J.-Y.; Hsu, C.-H.; Huang, Y.-F.; Chen, C.-C.; Li, S.-S.; Yeh, J. A.; Yao, D.-J.; Wang, Y.-L. (Appl. Phys. Lett., 2014)

(untitled) - Cai, X.; Gao, X.; Wang, L.; Wu, Q.; Lin, X. (Sens. Actuators, B, 2013)

(untitled) - Kakhki, S.; Barsan, M. M.; Shams, E.; Brett, C. M. A. (Anal. Methods, 2013)

(untitled) - Prakash, S.; Chakrabarty, T.; Singh, A. K.; Shahi, V. K. (Biosens. Bioelectron., 2013)

(untitled) - Srivastava, M.; Srivastava, S. K.; Nirala, N. R.; Prakash, R. (Anal. Methods, 2014)

(untitled) - Charan, C.; Shahi, V. K. (J. Appl. Electrochem., 2014)

(untitled) - Tong, Y.; Li, H.; Guan, H.; Zhao, J.; Majeed, S.; Anjum, S.; Liang, F.; Xu, G. (Biosens. Bioelectron., 2013)

(untitled) - Ahmadalinezhad, A.; Chen, A. (Biosens. Bioelectron., 2011)

(untitled) - Manjunatha, R.; Suresh, G. S.; Melo, J. S.; D’Souza, S. F.; Venkatesha, T. V. (Talanta, 2012)

(untitled) - Cao, S.; Zhang, L.; Chai, Y.; Yuan, R. (Talanta, 2013)

(untitled) - Gholivand, M. B.; Khodadadian, M. (Biosens. Bioelectron., 2014)

(untitled) - Li, J.; Peng, T.; Peng, Y. (Electroanalysis, 2003)

(untitled) - Gupta, V. K.; Norouzi, P.; Ganjali, H.; Faridbod, F.; Ganjali, M. R. (Electrochim. Acta, 2013)

(untitled) - Israr, M. Q.; Sadaf, J. R.; Asif, M. H.; Nur, O.; Willander, M.; Danielsson, B. (Thin Solid Films, 2010)

(untitled) - Sekretaryova, A. N.; Beni, V.; Eriksson, M.; Karyakin, A. A.; Turner, A. P. F.; Vagin, M. Y. (Anal. Chem., 2014)

(untitled) - Singh, J.; Roychoudhury, S.; Srivastava, M.; Solanki, P. R.; Lee, D. W.; Lee, S. H.; Malhotra, B. D. (Nanoscale, 2014)

(untitled) - Tsierkezos, N. G.; Ritter, U. (Phys. Chem. Liq., 2014)

(untitled) - Chiang, W.-H.; Chen, P.-Y.; Nien, P.-C.; Ho, K.-C. (Steroids, 2011)

(untitled) - Agnihotri, N.; Chowdhury, A. D.; De, A. (Biosens. Bioelectron., 2015)

(untitled) - Piletsky, S. A.; Piletskaya, E. V.; Sergeyeva, T. A.; Panasyuk, T. L.; El’skaya, A. V. (Sens. Actuators, B, 1999)

(untitled) - Shiigi, H.; Matsumoto, H.; Ota, I.; Nagaoka, T. (J. Flow Injection Anal., 2008)

(untitled) - Nagaoka, T.; Tokonami, S.; Shiigi, H.; Matsumoto, H.; Takagi, Y.; Takahashi, Y. (Anal. Sci., 2012)

(untitled) - Lee, Y.-J.; Kim, J.-D.; Park, J.-Y. (J. Korean Phys. Soc., 2009)

(untitled) - Li, Y.; Bai, H.; Liu, Q.; Bao, J.; Han, M.; Dai, Z. (Biosens. Bioelectron., 2010)

(untitled) - Lee, Y.-J.; Park, J.-Y. (Biosens. Bioelectron., 2010)

(untitled) - Ji, R.; Wang, L.; Wang, G.; Zhang, X. (Electrochim. Acta, 2014)